Effects of short-chain fatty acid-producing probiotic metabolites on symptom relief and intestinal barrier function in patients with irritable bowel syndrome: a double-blind, randomized controlled trial - Li, Erfeng; Wang, Jie; Guo, Bin; Zhang, Wenbin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundIBS often appears as bloating, altered bowel patterns, and abdominal pain (AP).Probiotics and SCFA may be useful in mucosal repair and symptom relief, according to earlier research, however there is currently a lack of systematic evidence supporting their therapeutic effectiveness across a variety of IBS subtypes.ObjectiveTo investigate the impacts of probiotics on signs and intestinal barrier function (IBF) in individuals with multiple IBS subtypes, and evaluate the role of SCFA in this process.MethodsA double-blind randomized controlled trial (DBRCT) design was adopted. Using the Rome IV criteria, a total of 120 individuals with IBS were randomised to either the probiotic group (PG) or placebo group (PLG). The intervention lasted for 12 weeks with an additional 4-week follow-up. In addition to fecal SCFA (FSCFA) levels, intestinal permeability (L/M ratio), tight junction proteins (TJP), serum/fecal inflammatory markers, and adverse event occurrence, the primary endpoint (PEP) evaluated was IBS Symptom Severity Scale (IBS-SSS) scores. Subgroup analysis was performed in selected cases.ResultsIn terms of symptom scores, there was a major correlation among group and time (F=9.314, P<0.001), and repeated-measures ANOVA showed that the PG’s scores were considerably < than those of the control group (CG) beginning in week 8 (all P<0.01). Levels of acetate, propionate, and butyrate considerably increased after 12 weeks of intervention (all P<0.01). Intestinal permeability and Occludin significantly improved at weeks 8 and 12 (all P<0.0167), while important differences in Claudin-1 and Zonulin appeared only at week 12 (all P<0.0167). Inflammatory markers considerably decreased at week 12 (all P<0.0167). There were no statistically significant differences in adherence or adverse events (P>0.05). Reductions in symptom scores were positively connected with an increase in SCFAs (r=0.43, P=0.002). Subgroup analysis across multiple IBS subtypes indicated significant symptom relief at week 12 for all subtypes (all P<0.05).ConclusionProbiotics significantly improved clinical symptoms in IBS patients of different subtypes by increasing short-chain fatty acid levels, repairing the intestinal barrier, and reducing inflammation.